Liquid fuel cells - Soloveichik, Grigorii L. (Beilstein Journal of Nanotechnology, 2014)
The advantages of liquid fuel cells (LFCs) over conventional hydrogen–oxygen fuel cells include a higher theoretical energy density and efficiency, a more convenient handling of the streams, and enhanced safety. This review focuses on the use of different types of organic fuels as an anode material for LFCs. An overview of the current state of the art and recent trends in the development of LFC and the challenges of their practical implementation are presented.
Keywords: anion exchange membranes; direct alcohol fuel cells; direct borohydride fuel cells; electrocatalysts; liquid fuel cells; organic fuel; proton exchange membranes